Lotta Village Social Empowerment Through Aquaponic Urban Farming in Sentrum Agraris Lotta: Pemberdayaan Masyarakat Desa Lotta Melalui Urban Farming Akuaponik di Sentrum Agraris Lotta - Moko, Emma Mauren; Rawung, Livana Dethris; Rahardiyan, Dino; Sitanayah, Lanny; Lihiang, Anatje; wa, Johanna Zusye (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Urban farming, an agricultural concept utilizing limited space. This application is fititng for urban and suburban scapes with limited agricultural fields like Lotta village, located in the suburbans of Manado city. Sentrum Agraris Lotta (SAL), a non profit organization that functions as the societies eduction hub in organic agricultur, SAL has facilitated this aquaponic implementation as an empowerment and mentoring activity for the PKK and Local Government of Lotta Village, Pineleng District of Minahasa Regency. Integrating vegetable farming with fish farming, this activity serves as a vesel for the KKN MBKM students progam. This activity elevated social empowerments by practical skills impartment to the district and partnering organizations, while disseminating the society on food security and household economy. Also a media for students in implementing science and social engagement in an off-campus practical activity as one of the parameter of the main higher education performance indicators (IKU-PT).